Exploring the Personality Profile of Effective School Principals: Teachers’ Perspectives from Junior High Schools in South Sulawesi - Usman, Usman; Imron Burhan (International journal of technology and education research, 2025)
The quality of education in Indonesia remains a major challenge, with school leadership playing a crucial role in determining educational success. This study explores the personality profiles of effective school principals in junior high schools in South Sulawesi based on teachers’ perspectives. Using a quantitative descriptive approach, data were gathered through teacher evaluations to identify key personality dimensions such as extraversion, agreeableness, emotional stability, and openness. The findings reveal that agreeableness, emotional stability, and openness are the most dominant traits associated with effective principals. Principals who are open to new ideas, emotionally balanced, and empathetic toward teachers are perceived to create positive school climates and enhance teacher motivation. These results suggest that personality characteristics significantly influence leadership effectiveness and school performance. The study recommends that personality assessment be integrated into principal recruitment and professional development to improve leadership quality and educational outcomes in Indonesia.